Efficient Interfacial Upconversion Enabling Bright Emission at an Extremely Low Driving Voltage in Organic Light‐Emitting Diodes. Issue 4 (6th January 2022) - Izawa, Seiichiro; Morimoto, Masahiro; Naka, Shigeki; Hiramoto, Masahiro
Abstract: A remaining frontier in the field of organic light‐emitting diodes (OLEDs) is reducing their operating voltage. Herein, an efficient OLED is reported, operable by a 1.5 V battery, that produces bright emission equivalent to the luminance of a typical display. The OLED has a smaller turn‐on voltage at 0.97 V than an optical energy of emitted photons at 2.04 eV (608 nm), because the OLED is based on an upconversion (UC) transition associated with triplet–triplet annihilation that doubles the energy of excited states. The characteristics of charge transfer (CT) state at the interface have been revealed, which are key to efficient UC, and the percentage of excited states deactivated by parasitic loss processes during the UC transition is significantly reduced from over 90% to approximately 10% by introducing a highly crystalline acceptor material and an emissive dopant. Consequently, the UC‐OLED achieves a quantum efficiency that is two orders of magnitude higher than that in the previous report. Abstract : An efficient organic light‐emitting diode (OLED) operable by a 1.5 V battery that produces bright emission equivalent to the luminance of a typical display is reported. The OLED is based on an upconversion (UC) transition near its donor/acceptor interface. The efficient UC is realized by controlling a character of a charge transfer state, which is a key intermediate.